2009
DOI: 10.3346/jkms.2009.24.3.493
|View full text |Cite
|
Sign up to set email alerts
|

Differential Methylation Pattern of ID4, SFRP1, and SHP1 between Acute Myeloid Leukemia and Chronic Myeloid Leukemia

Abstract: To gain insight into the differential mechanism of gene promoter hypermethylation in acute and chronic leukemia, we identified the methylation status on one part of 5'CpG rich region of 8 genes, DAB2IP, DLC-1, H-cadherin, ID4, Integrin α4, RUNX3, SFRP1, and SHP1 in bone marrows from acute myeloid leukemia (AML) and chronic myeloid leukemia (CML) patients. Also, we compared the methylation status of genes in AML and CML using methylation-specific PCR (MSP). The frequencies of DNA methylation of ID4, SFRP1, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 26 publications
2
16
0
Order By: Relevance
“…Interestingly, SHP-1 protein levels have been found reduced both in several types of hematopoietic tumors [21][22][23]35 and in patients with advanced stage CML with a DNA methylation independent process. 24 Instead, we demonstrate that in the resistant CML cell line the low expression of SHP-1 is strongly associated with hypermethylation status of its promoter region, as previously shown both in patients with acute myeloid leukemia and patients with CML.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Interestingly, SHP-1 protein levels have been found reduced both in several types of hematopoietic tumors [21][22][23]35 and in patients with advanced stage CML with a DNA methylation independent process. 24 Instead, we demonstrate that in the resistant CML cell line the low expression of SHP-1 is strongly associated with hypermethylation status of its promoter region, as previously shown both in patients with acute myeloid leukemia and patients with CML.…”
Section: Discussionmentioning
confidence: 99%
“…24 Instead, we demonstrate that in the resistant CML cell line the low expression of SHP-1 is strongly associated with hypermethylation status of its promoter region, as previously shown both in patients with acute myeloid leukemia and patients with CML. 23 Indeed, the exposure of the resistant cell line to a demethylating agent can revert this suppression. We demonstrate that, in both the resistant and the sensitive KCL22 cell lines, the activity of the BCR-ABL is completely suppressed by IMA exposure.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The methylation status of the SHP1 promoter is associated with gene dormancy, which is an important mechanism in the development of lymphoma and leukaemia. SHP1 protein expression was completely absent or partially reduced in the majority of types of lymphoma and leukaemia cell lines, such as YS2, IWA3, NK, TomJim, MTI, EDS, and ATLIK (11,12). The present study demonstrated the lack of SHP1 expression in K562 cells.…”
Section: Discussionmentioning
confidence: 62%